(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Silicon-organic (Si-organic) coatings exhibit exceptional thermal stability, chemical resistance, and adhesion on metal, ceramic, and glass substrates, making them indispensable in high-temperature industrial applications. This paper presents a comprehensive study on the synthesis, characterization, and performance of high-temperature resistant Si-organic coatings. The coatings are prepared using siloxane prepolymers and functional organic modifiers, with the incorporation of inorganic fillers to enhance thermal and mechanical performance.